Applying fuzzy contrast enhancement on earthquake impact images - Suzelawati Zenian; Rodeano Roslee (IOP Publishing Ltd, 2022)
In this paper, fuzzy contrast enhancement technique is applied on earthquake impact images in Ranau, Sabah. The aim is to highlight the visible differences between adjacent structures in the images. The brightness differences between objects and its background is enhanced to improve the visibility. In fuzzy approach, the gray plane is mapped into fuzzy plane by using membership function. The membership values represent the degree of brightness or darkness of the pixels.